Activation of Nrf2 in Astrocytes Suppressed PD-Like Phenotypes via Antioxidant and Autophagy Pathways in Rat and Drosophila Models. - Guo, Q.; Wang, B.; Wang, X.; Smith, W.W.; Zhu, Y.; Liu, Z. (Cells, 2021)
The oxidative-stress-induced impairment of autophagy plays a critical role in the pathogenesis of Parkinson's disease (PD). In this study, we investigated whether the alteration of Nrf2 in astrocytes protected against 6-OHDA (6-hydroxydopamine)- and rotenone-induced PD-like phenotypes, using 6-OHDA-induced rat PD and rotenone-induced Drosophila PD models. In the PD rat model, we found that Nrf2 expression was significantly higher in astrocytes than in neurons. CDDO-Me (CDDO methyl ester, an Nrf2 inducer) administration attenuated PD-like neurodegeneration mainly through Nrf2 activation in astrocytes by activating the antioxidant signaling pathway and enhancing autophagy in the substantia nigra and striatum. In the PD Drosophila model, the overexpression of Nrf2 in glial cells displayed more protective effects than such overexpression in neurons. Increased Nrf2 expression in glial cells significantly reduced oxidative stress and enhanced autophagy in the brain tissue. The administration of the Nrf2 inhibitor ML385 reduced the neuroprotective effect of Nrf2 through the inhibition of the antioxidant signaling pathway and autophagy pathway. The autophagy inhibitor 3-MA partially reduced the neuroprotective effect of Nrf2 through the inhibition of the autophagy pathway, but not the antioxidant signaling pathway. Moreover, Nrf2 knockdown caused neurodegeneration in flies. Treatment with CDDO-Me attenuated the Nrf2-knockdown-induced degeneration in the flies through the activation of the antioxidant signaling pathway and increased autophagy. An autophagy inducer, rapamycin, partially rescued the neurodegeneration in Nrf2-knockdown Drosophila by enhancing autophagy. Our results indicate that the activation of the Nrf2-linked signaling pathways in glial cells plays an important neuroprotective role in PD models. Our findings not only provide a novel insight into the mechanisms of Nrf2-antioxidant-autophagy signaling, but also provide potential targets for PD interventions.